2013
DOI: 10.1371/annotation/2f278ed8-d5e7-440a-9e49-c8d1df20d1f1
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Molecular Vibration-Sensing Component in Human Olfaction

Abstract: Whether olfaction recognizes odorants by their shape, their molecular vibrations, or both remains an open and controversial question. A convenient way to address it is to test for odor character differences between deuterated and undeuterated odorant isotopomers, since these have identical ground-state conformations but different vibrational modes. In a previous paper Proc Natl Acad Sci USA 108:9, 3797-802) we showed that fruit flies can recognize the presence of deuterium in odorants by a vibrational mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
(24 reference statements)
0
9
0
Order By: Relevance
“…Since smelling peaks as they come out of a gas chromatograph is a difficult skill, a peak capture method invented by Christina Zelano was used, akin to preparative GC but on a microscale. The results conclusively showed an odour character difference perceptible by untrained subjects [75]. One of us (LT) was a subject and reports that the odour difference was very marked insofar as the musky odour character was absent from the nominally perdeuterated samples, replaced by a harsh (often described as waxy) burnt-candle smell.…”
Section: Mammalsmentioning
confidence: 63%
See 3 more Smart Citations
“…Since smelling peaks as they come out of a gas chromatograph is a difficult skill, a peak capture method invented by Christina Zelano was used, akin to preparative GC but on a microscale. The results conclusively showed an odour character difference perceptible by untrained subjects [75]. One of us (LT) was a subject and reports that the odour difference was very marked insofar as the musky odour character was absent from the nominally perdeuterated samples, replaced by a harsh (often described as waxy) burnt-candle smell.…”
Section: Mammalsmentioning
confidence: 63%
“…Modification of the fingerprint region, by contrast, is most easily achieved by deuteration of part or all the hydrogens contained in the odourant. As we have seen, it has been shown that flies [87,122], honeybees [88,90], and humans [75] can tell hydrogen from deuterium odourants. Remarkably, a connection between fingerprint and functional group regions was also found when flies who had been trained to avoid deuterium odourants also avoided nitriles and vice versa, suggesting that the -CD stretch and -CN stretch, both around 2150 cm −1 were being confused by the flies [87].…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…These flies were also trained to react to specific levels of deuterated vs. natural abundance species through application of negative electronic stimulus in a similar T-maze. A generalization experiment was also performed showing that Drosophila trained to avoid 1-octanol vs. d 17 -1-octanol were able to generalize some characteristics and showed selective avoidance for ACP vs. Gane et al [88,89] examined the VTO through two tests employing both trained and untrained human subjects. Furthermore, great effort was expended to address the concern of impurities; assuring GC-level purities of all odorants, even those purchased at high purity.…”
Section: Methodsmentioning
confidence: 99%